A fast-response framework for real-time 3D wind field reconstruction: Supporting urban air mobility applications in complex environments - Zihao Pang; Junxia Gu; Quanqian Xu; Shuai Han; Lanxin Luo; Zhiqiang Zhang; Zhi Zhu; Tao Zhang; Yaping Ma; Dongdong Shen (Sustainable Cities and Society, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Temperature-constrained sorption of inorganic and organic selenium by Fe-oxide minerals: Significance for selenium bioavailability in Earth's critical zone - Kunfu Pi; Qianyong Liang; Yiqun Gan; Yaping Zhang; Tao Gu; Li Zhang (Applied Geochemistry, 2026)

Inversion of aboveground biomass of Spartina alterniflora based on multispectral UAV - Ziyao Chen; Yan Gu; Jianchun Chen; Dingchen Liu; Junjie Rui; Shibing Zhu; Yaping Wang (Acta Oceanologica Sinica, 2025)

Analysis of Common Genetic Variation of Anxiety Disorders in Essential Tremor - Yaping Yan; Lanxiao Cao; Luyan Gu; Congying Xu; Jinyu Lu; Dayao Lv; Jun Tian; Xinzhen Yin; Jiali Pu; Baorong Zhang; Guohua Zhao (Journal of Molecular Neuroscience, 2025)

How does high hydrostatic pressure treatment improve the esterification of quinoa (Chenopodium quinoa Willd.) starch? - Yaping Yin; Yongliang Zhuang; Liping Sun; Ying Gu; Gaopeng Zhang; Xuejing Fan; Yangyue Ding (Food Chemistry, 2025)

One-step synthesis of iron and carbon-quantum-dot co-decorated graphitic carbon nitride photocatalysts for carbamazepine degradation - Xiaoli Liu; Yaping Wang; Yutao Xie; Tiefeng Xu; Yan Gu; Wangyang Lu (Journal of Environmental Chemical Engineering, 2024)

One-step hydrothermal synthesis of nitrogen-doped carbon-quantum-dots for detection and efficient removal of high-concentrations nicotine from tobacco wastewater under visible light - Xiaoli Liu; Yaping Wang; Yan Gu; Wangyang Lu (Chemical Engineering Journal, 2024)

Compound carbon policy for promoting low-carbon technology innovation in enterprises considering government supervision - Qianqian Gu; Lei Hang; Yaping Jiang (Environment, Development and Sustainability, 2024)

Identification and analysis of alleles in the aroma biosynthesis pathways based on Camellia sinensis ‘Jinguanyin’ haplotype-resolved genomes - Mengya Gu; Ting Gao; Mengting Xu; Yaping Hong; Yibin Wang; Jiaxin Yu; Yuhang Zhang; Wenqin She; Pengjie Wang; Naixing Ye (Trees, 2023)

Association Analysis of 27 Single Nucleotide Polymorphisms in a Chinese Population with Essential Tremor - Lanxiao Cao; Luyan Gu; Jiali Pu; Dayao Lv; Jun Tian; Xinzhen Yin; Ting Gao; Zhe Song; Jinyu Lu; Gaohua Zhao; Baorong Zhang; Yaping Yan; et al. (Journal of Molecular Neuroscience, 2023)

Effects of low-protein-high-starch diet on growth performance, glucose and lipid metabolism of Amur sturgeon (Acipenser schrenckii) during feeding and starvation phases - Xiaoran Zhang; Yaping Zhu; Hongcheng Wei; Xu Gu; Xiufeng Wu; Min Xue; Xiaofang Liang (Aquaculture, 2023)

Correction to: Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Jun Wang; Xuexia Zhu; Yunfei Sun; Lei Gu; Yaping Wu; Yafen Chen; Zhou Yang (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus ( T. obscurus ), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Removal of Trace As(V) from Water with the Titanium Dioxide/ACF Composite Electrode - Liang Peng; Yaping Chen; Hong Dong; Qingru Zeng; Huijuan Song; Liyuan Chai; Ji-dong Gu (Water, Air, & Soil Pollution, 2015)

Removal of trace Cd(II) from water with the manganese oxides/ACF composite electrode - Yaping Chen; Liang Peng; Qingru Zeng; Yang Yang; Ming Lei; Huijuan Song; Liyuan Chai; Jidong Gu (Clean Technologies and Environmental Policy, 2015)

Directed Self-assembled Nanoparticles of Probucol Improve Oral Delivery: Fabrication, Performance and Correlation - Zhiwen Zhang; Shijun Jiang; Zeying Liu; Baohua Niu; Wangwen Gu; Yaping Li; Jingbin Cui (Pharmaceutical Research, 2014)

Growth hormone signalling and apoptosis in neonatal rat cardiomyocytes - Yaping Gu; Yunzeng Zou; Ryuichi Aikawa; Doubun Hayashi; Sumiyo Kudoh; Toshimasa Yamauchi; Hiroki Uozumi; Weidong Zhu; Takashi Kadowaki; Yoshio Yazaki; Issei Komuro (Molecular and Cellular Biochemistry, 2001)